Brood reduction caused by sibling cannibalism in Isodontia harmandi (Hymenoptera: Sphecidae), a solitary wasp species building communal brood cells - Imasaki, Yui; Endo, Tomoji (PLOS ONE, 2022)
Sibling rivalry or brood reduction prevailing within bird nests is effectively avoided in solitary aculeate nests because the larvae of wasps and bees usually develop in each brood cell. However, a solitary wasp species, Isodontia harmandi, allows us to study brood reduction in a communal brood cell, where up to a dozen larvae develop in a group relying on prey provisioned by a female wasp. To demonstrate brood reduction in this species, we collected nests at various developmental brood stages from fields for five years (2010–2015). There was a significant decrease in the brood size between the nests sampled at the egg or hatchling stages and those at later stages when analyzing only data excluding nests that were parasitized, attacked by predators, or containing deteriorated prey. In whole brood-rearing experiments, we also confirmed that brood reduction occurred in 30 of 39 nests during larval stages and in 23 nests after cocoon stage. Larval survival was affected positively by total prey weight and negatively by brood size, though cocoon survival was not affected. A third-quarter (76%) of larval death was identified as sibling cannibalism through observation by time-lapse recording on multi-larvae rearing experiments. Therefore, we conclude that brood reduction routinely occurs as a result of sibling cannibalism in I. harmandi. Additionally, as we could not detect any positive effects of clutch size on the amount of provision, female wasps might overproduce offspring due to the unpredictability of available prey resources. Differences in brood size and reduction among sex categories were undetected, except for parental provisions. Thus, sibling cannibalism may efficiently regulate brood size in communal brood cells under prey shortage.